Lyapunov-based switching supervisory control of nonlinear uncertain systems - Angeli,D; Mosca,E (IEEE Transactions on Automatic Control, 2002)
Switching supervisory control (SSC) algorithms was developed for nonlinear plants with uncertain parameters and subjected to unaccessible persistent disturbances of known maximum size. The algorithm provided that full state feedback was available and can be tailored for linear plant dynamics. A simulative example was presented which showed that the algorithm was capable to cope with slowly time-varying and piecewise constant parameters.